Pacing strategies during repeated maximal voluntary contractions - Halperin, I.; Aboodarda, S. J.; Basset, F. A.; Byrne, J. M.; Behm, D. G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Purpose: Pacing strategies have been reported to occur during continuous cyclical exercises. However, currently no studies have examined if pacing takes place during repeated maximal voluntary isometric muscle contractions (MVICs). Accordingly, the purpose of this study was to examine if informing subjects on the number of MVICs they would perform would affect force, root mean squared electromyography (EMG), rating of perceived exertion (RPE) and evoked twitch properties during similar fatiguing protocols. Methods: Thirty well trained male subjects completed 3 fatiguing protocols in a randomized order. In the Control condition participants were informed they would perform twelve MVICs, and then completed all twelve. In the Unknown condition they were not told how many MVICs they would perform but were stopped after twelve. Lastly, In the Deception condition they were initially told they would perform only 6 MVICs, but after the 6th contraction they were asked to perform a few more repetitions and were stopped after twelve. Results: Compared to the Unknown condition, subjects demonstrated greater forces (p<0.05, ES=0.35-1.14, 2-7.5%) and biceps EMG (p<0.05, ES=0.6, 6%) in the Deception condition during the first 6 MVICs. Additionally, under all conditions subjects applied greater forces in the last repetition (#12) relative to the previous one (#11) (p<0.05, ES=0.36-0.5, 2.8-3.8%). No significant differences were found in evoked twitch properties and RPE between conditions. Conclusions: The anticipation of performing fewer MVICs led to increased force, whereas force decreased when no end point was provided. The results also question the assumption that subjects followed the instruction to exert maximal effort during repeated MVICs.